Prognostic factors and survivals of children with steroid-resistant nephrotic syndrome - Partini Pudjiastuti Trihono; Nina Dwi Putri; Aman B Pulungan (Indonesian Pediatric Society, 2013)
Background Children with steroid resistant nephrotic syndrome(SRNS) generally survive, although during the course of diseasetheir kidney function may decrease, leading to end-stage renaldisease (ESRD). There have been few studies reporting on thesurvivals of children with SRNS.Objectives To determine patient and kidney survival rates in childrenwith SRNS at the first, second, third, fourth, and fifth years; and toevaluate the effects of age at onset, initial kidney function, hypertension,and type of resistance, on the survivals of children with SRNS.Methods This retrospective cohort study was performed usingsecondary data obtained from medical records of patients with SRNS inDepartment of Child Health, Cipto Mangunkusumo Hospira between2004-2011. The outcomes of kidney survivals were defined in two ways:lack of doubling of base creatinine levels and lack of ESRD.Results There were 45 children with SRNS in our study. Their medianduration ofillness was 24 (range 12-95) months. Twenty percent of thesubjects died, 31.1 % had a doublingofbase creatinine levels, and 13.4%developed ESRD. Life survival rates of subjects at the first, second,third, fourth, and fifth years after diagnosis were 93 %, 84%, 80